Studi Literatur Digitalisasi Model 5A untuk Pengendalian Obesitas Saat Pandemi COVID-19 - Florentina Dewi Pramesuari; Daniel Aryo Wibowo; Ezra Clement Lie; Jessica Christanti (Soegijapranata Catholic University, 2021)
The COVID-19 pandemic has had an impact on health regulations made by WHO and the Indonesian Ministry of Health. Recent studies have shown a significant association with self-isolation and behavioral changes such as decreased physical activity and decreased diet with risk of obesity. The existence of social media and mobile apps as a medium of communication can help change lifestyle behaviors and unhealthy diet patterns. The purpose of study was to collect and analize healthcare digitalization articles especially obesity management and 5A model. The study method was literature review. Fulltext Articles was collected from google scholar and pubmed with some keywords such as obesity, epidemiology, COVID-19, pandemic, technology, communication, education, promotion, prevention. The result stated that the digitalization of obesity management with social media and machine learning mobile app could increase patients independence to improve their weight such as behaviour change, lifestyle and dietary pattern.